Optimum criterion to be dependable in early cholecystectomy in acute calculous cholecystitis (Eurasian Medical Research Periodical, 2022)
Early cholecystectomy in acute cholecystitis is still avoided by many surgeons due to discrepancy in knowledge available about the management options when dealing with acute cholecystitis and the lack of suitable and considrable criterion to be depend on when choosing early cholecystectomy as an preferred option. So, in this study , the analytic hierarchy process is used to investigate the most optimum criterion that can be depended when choosing early appraoch in cholecstectomy cases. The study data had been supplied by a four expert consultant surgeons working at baqubah teaching hospital with excelent expereince about cholecystectomy cases. The investigated criteria involve intraopertive complications (bleeding,common bile duct injury, visceral injury), operative time, postoperative compilcations(wound infection, intraabdominal infection,bile leak,deep venous thrombosis) and length of Stay in the Hospital. The experts give an optimum weight for each criterion on a multiple comaparison scales. The intraopertive complications have the highest mean value recorded and is equal to 0.353 for cholecystectomies done within 3 days of onset of acute cholecystitis and is equal to 0.471 for cholecystectomies done within 7 days of onset of acute cholecystitis and so the intraopertive complications represent the optimum and the most dependable criterion when choosing early cholecystectomy as an approach of choice to treat acute cholecystitis